Numeral incorporating roots in numeral systems: a comparative analysis on two sign languages - Fuentes, Mariana (2010)
Numeral incorporating roots in the numeral systems of Argentine Sign Language and Catalan Sign Language are described and compared, as well as the main features of both languages’ number systems. Participant observation has been carried out in both languages, in most cases in natural contexts where informants discussed the use of numerals and roots. Ten informants took part in LSC data collection and six in LSA data collection. Data were corroborated by analyzing the videos available at www.youtube.com/confargsordos for LSA, and the videos and books provided by the ILLESCAT Foundation for LSC, and previous research. A general inventory of roots in both languages and specifically of roots in both numerals systems was carried out. The role of roots in the formation of ordinals and cardinals and the main features of both number systems are described. Data suggest that numeral incorporating roots in the number systems of these two sign languages are formed only from numerals that do not derive from manual counting. This assumption is discussed and further research about this point is emphasized.